Растрепанный воробей: Сказки / К. Г. Паустовский ; худож. В. Цигаля - Паустовский Константин Георгиевич (Детская литература, 1986)
3-4кл Экземпляры: аб. ЦБ (20201207) / Инвентарный номер: 10064 / Авт.знак: П21 / ББК: 84(2Рос)